2007
DOI: 10.1016/s0828-282x(07)70864-4
|View full text |Cite
|
Sign up to set email alerts
|

Right atrial infarction, atrial arrhythmia and inferior myocardial infarction form a missed triad: A case report and review of the literature

Abstract: Atrial infarction is rarely diagnosed before death because of its characteristically subtle and nonspecific electrocardiographic findings. These findings may be overshadowed by changes associated with concomitant ventricular infarction. A case of right atrial infarction accompanied by inferior myocardial infarction with rapid decompensated atrial fibrillation is reported. To increase awareness and knowledge of a complicated diagnosis, the present case is described in the context of a review of the relevant lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 9 publications
2
13
0
2
Order By: Relevance
“…This difference was more significant in inferior leads than in other leads. Regardless of whether ATMI is isolated or not, it may cause complications, such as heart failure, arrhythmia, thromboembolic events, and even death as a result of atrial free‐wall rupture . We suggest that atrial ischemia occurring with inferior‐wall STEMI causes a slow conduction and a disruption of homogeneity in the atrial tissue.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…This difference was more significant in inferior leads than in other leads. Regardless of whether ATMI is isolated or not, it may cause complications, such as heart failure, arrhythmia, thromboembolic events, and even death as a result of atrial free‐wall rupture . We suggest that atrial ischemia occurring with inferior‐wall STEMI causes a slow conduction and a disruption of homogeneity in the atrial tissue.…”
Section: Discussionmentioning
confidence: 86%
“…As in the pathophysiology of ST‐segment deviation observed in ventricular MI, PR‐segment deviation is also expected in atrial ischemia or injury. Theoretically, it is possible to understand whether ATMI was biatrial or confined in a single atrium by specifically checking limb derivations . However, PR‐segment deviation was reported to not be a finding specific to atrial ischemia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 The first case of atrial infarction was described in 1925, while later research has shown a frequency ranging from 0.7% in antemortem up to 42% in autopsy studies. 2 Due to the large number of anastomotic branches of the coronary arteries, as well as the presence of oxygenated blood in the cavity of the left atrium, right atrial infarctions are four to five times more prevalent than those in the left atrium. 3,4 They cannot easily be verified on ECG and some of the changes combine elevation and depression of PT segments, often accompanied by atrial arrhythmias (flutter and fibrillation), a prolonged PR interval and abnormal Q-wave and P-wave axis changes.…”
Section: Introductionmentioning
confidence: 99%